One-pot synthesis of a carbon dots@zeolitic imidazolate framework-8 composite for enhanced Cu2+ sensing. Issue 32 (6th August 2020) - Guo, Hao; Wang, Xiaoqiong; Wu, Ning; Xu, Mengni; Wang, Mingyue; Zhang, Longwen; Yang, Wu
Abstract : A novel composite (CDs@ZIF-8) based on carbon dots (CDs) and a zeolitic imidazolate framework (ZIF-8) was successfully synthesized by encapsulating CDs into the pores of ZIF-8 through a simple one-pot solvothermal method. Abstract : A novel composite (CDs@ZIF-8) based on carbon dots (CDs) and zeolitic imidazolate framework (ZIF-8) was successfully synthesized by encapsulating CDs into the pores of ZIF-8 through a simple one-pot solvothermal method. The as-synthesized CDs@ZIF-8 inherited simultaneously the strong adsorption capacity of ZIF-8 and the excellent optical properties of CDs. The composite exhibited excellent dispersibility and high structural and fluorescence stability in aqueous solution, which could be employed as an excellent turn-off mode fluorescent probe to detect Cu 2+ . The large specific surface area and strong adsorption properties of ZIF-8 enabled the resultant composite to effectively enrich Cu 2+ for further improving the analytical sensitivity. The possible fluorescence quenching mechanism has also been discussed in detail and it was found that the effective fluorescence quenching of Cu 2+ to CDs@ZIF-8 could be attributed to the strong ability of Cu 2+ to combine with the carboxyl group or amino group on the CD surface and the strong adsorption capacity of ZIF-8; their synergistic effect resulted in effective fluorescence quenching.